Keefektifan Media Pembelajaran Papan Pecahan dalam Pembelajaran Materi Pecahan di Sekolah Dasar - Mutiara Mutiara; Saleh, Sitti fithriani; Hadaming, Hamdana (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the effectiveness of using fractional board learning media on student learning outcomes in learning mathematics fraction material in class III SDN 62 Palisi. Effectiveness is viewed from 4 aspects, namely: completeness of student learning outcomes, student activity, teacher's ability to manage learning, and student responses. The type of research used is pre-experimental research. The research design used was The One Group pretest posttest Design. Data collection techniques in this study were carried out using tests, observations, and questionnaires. The results showed that (1) all students had achieved individual learning mastery and this meant that classical learning mastery had been achieved, (2) the average percentage of student activity frequency reached the active criterion of 91.66%, (3) the average percentage the frequency of the teacher's ability to manage learning reached the high criterion of 3.4, (4) the positive response questionnaire from students reached 96.4%. From the results of this study it can be concluded that fractional board media is effectively used in learning mathematics fraction material in class IIIA students at SDN 62 Palisi.